Microbial Diversity and Evidence of Novel Homoacetogens in the Gut of Both Geriatric and Adult Giant Pandas (Ailuropoda melanoleuca) - Tun, Hein Min (Public Library of Science, 2014)
Recent studies have described the bacterial community residing in the guts of giant pandas, together with the presence of lignocellulolytic enzymes. However, a more comprehensive understanding of the intestinal microbial composition and its functional capacity in giant pandas remains a major goal. Here, we conducted a comparison of bacterial, fungal and homoacetogenic microbial communities from fecal samples taken from two geriatric and two adult captive giant pandas. 16S rDNA amplicon pyrosequencing revealed that Firmicutes and Proteobacteria are the most abundant microbiota in both geriatric and adult giant pandas. However, members of phylum Actinobacteria found in adult giant pandas were absent in their geriatric counterparts. Similarly, ITS1 amplicon pyrosequencing identified developmental changes in the most abundant fungal classes from Sordariomycetes in adult pandas to Saccharomycetes in geriatric pandas. Geriatric pandas exhibited significantly higher abundance of a potential probiotic fungus (Candida tropicalis) as compared to adult pandas, indicating their importance in the normal digestive physiology of aged pandas. Our study also reported the presence of a lignocellulolytic white-rot fungus, Perenniporia medulla-panis, and the evidence of novel homoacetogens residing in the guts of giant pandas.